Ethnomedicinal Study and Thin Layer Chromatography Confirmation of Medicinal Plants to Treat Digestive Disorders in Medong Village, Pandeglang, Banten - Rindita Rindita; Supandi Supandi; Nuriza Rahmadini; Daffa Nur Fadhlurrohman; Syilbi Ayu Riani (Journal of Food and Pharmaceutical Sciences, 2026)
Medicinal plants with anti-ulcer and anti-diarrheal properties are often used by the community to treat digestive disorders in Medong Village, Pandeglang, Banten, but have not been well recorded. The purpose of this study was to document the types of plants used as traditional medicine to treat ulcers and diarrhea, and to identify secondary metabolite compounds using thin-layer chromatography (TLC). Sampling was conducted using purposive and snowball sampling methods with 70 informants. Quantitative data analysis was carried out by calculating the use value (UV). The results of data collection from 70 informants identified 15 plant species used as anti-ulcer and antidiarrheal agents. Based on the highest UV value, guava leaves and turmeric had the highest UV as antidiarrheal, and red leaf had the lowest. For treating ulcers, turmeric and nangka walanda leaves have the highest UV, and mamangkokan (Polyscias scutellaria) has the lowest. The parts of the plant that are often used as medicine are leaves, rhizomes, and herbs. Phytochemical screening showed that almost all samples contained secondary metabolite compounds that have antidiarrheal and antiulcer activity, namely flavonoids and tannins, and their presence was confirmed using TLC, with Rf values within the standard value range.